The Effectiveness of Group Guidance with Cinematherapy and Role-Playing Techniques to Improve Prosocial Behavior - Herfidawati, Intan; Eddi Wibowo, Mungin; Purwanto, Edy (Study Program of Guidance and Counseling, Postgraduate Program, Universitas Negeri Semarang, 2021)
Prosocial development is strongly related to various positive development for students, including academic success, personal achievement, positive relationship with others, and higher social competence. However, some adolescents remain doing antisocial behavior. Thus, this study attempted to examine the effectiveness of a group guidance service with cinematherapy, role playing, and the combination of cinematherapy and role-playing techniques to improve the prosocial behavior of Vocational High School (SMK) students. To do so, it used an experimental design of Randomized Pretest-Posttest Comparison Group by involving 30 students divided into three groups with 10 students in each. Based on Wilcoxon test results, the guidance group with both cinematherapy and role-playing techniques was effective to improve prosocial behavior indicated by the results of (Z=2.81, p<0.05) for cinematherapy, and (Z=2.81, p<0.05) for role playing. In the same way, the combination of both techniques was effective to improve prosocial behavior by gaining (Z=2.81, p<0.05). Additionally, the results of Kruskal Wallis test showed no significant difference in the level of effectiveness of the group with cinematherapy, role playing, and the combination of both techniques, namely (x2=0.23, p>0.05). These findings are expected to encourage counselors to conduct group guidance with cinematherapy and role-playing techniques to improve prosocial behavior.